Internship application system (IAS) for university students using laravel / Alif Faisal Ibrahim, Norshazwanie Musa and Muhammad Nabil Fikri Jamaludin - Ibrahim, Alif Faisal; Musa, Norshazwanie; Jamaludin, Muhammad Nabil Fikri (UiTM Cawangan Perlis, 2018)
Industrial training or internship is an important part of a study program for all university students in Malaysia. The current system is done manually where students must apply for internship by filling in paper forms. The purpose of the study is to design, develop and evaluate the Internship Application System (IAS) for university students using Laravel PHP framework. Laravel is a fully-fledged Model View Controller (MVC) framework chosen due to many features it supports, which are valuable set of characteristics which will speed up web development and create powerful, interactive layouts with the contents. Agile methodology was implemented as the research methodology for this study. This methodology consists of five phases which are requirement, planning, design, develop and release. The study is using both functionality and usability test in release phases, which involves coordinators and students as participants. A questionnaire was given to each participant to evaluate the usability of IAS. As a result, most participants agreed that using the developed system can improve internship application process.